EDUKASI PENGGUNAAN OBAT SALURAN PENCERNAAN (GASTRITIS) PADA SANTRI P2S2 SUKOREJO - Gasim Soka, Burhanudin (Jurnal Pengabdian Masyarakat Berkarya, 2025)
Gastritis is a condition of inflammation of the stomach lining that is often triggered by an irregular lifestyle and eating habits. The community service activity entitled ‘Education on the Use of Digestive Tract Medication (Gastritis) for P2S2 Sukorejo Students’ was carried out using a socialisation method. The objectives were: (1) to enhance students' knowledge about gastritis, including its causes, symptoms, and management; and (2) to provide an understanding of the types of medications used to treat gastritis and their proper usage. The process began with the distribution of pre-test questionnaires, followed by a presentation of the material by the presenter, an interactive question-and-answer session, and concluded with the completion of post-test questionnaires to measure the impact and benefits of the activity. The evaluation results showed a significant increase in participants' knowledge. 100% of respondents stated that they understood the material on gastritis, 97.1% stated that they knew about healthy eating and lifestyle patterns, and 100% of respondents admitted to understanding the types and use of medications for gastritis therapy. Overall, all respondents (100%) rated the activity as beneficial, and 97.1% stated that the material was presented clearly.